IMPLEMENTASI KETERBUKAAN INFORMASI PUBLIK DALAM MEWUJUDKAN GOOD LOCAL GOVERNANCE DI NAGARI. LAWANG MANDAHILING KECAMATAN.SALIMPAUNG KABUPATENTANAHDATAR - Fajar G, Djorgi; Maijar, Andri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research is based on the government's emphasis on the aspect of openness of public information in the implementation of government bureaucracy and also through transparency which will be applied to the community in the implementation of good local governance. The research focus in this study is how to implement public information openness in realizing good local governance in Nagari Lawang Mandahiling, Salimpaung District, Tanah Datar Regency. The aim of this research is to find out how to implement public information openness in realizing good local governance in Nagari Lawang Mandahiling. This research uses a qualitative descriptive research method. The data collection techniques used were observation, interviews and documentation. The source of this research was interviews with the Wali of Nagari Lawang Mandahiling then the Nagari Apparatus then the Chairman of KAN Nagari Lawang Mandahiling and several members of the community. To see the validity of the data, researchers used triangulation. Based on the results of research in Nagari Lawang Mandahiling, 1) Process and delivery of information in Nagari Lawang Mandahiling through information boards, announcements in mosques and through the head of Jorong in Nagari. 2) implementation of public information disclosure in Nagari Lawang Mandahiling integrating the principles of Good Governance in every aspect of its government. Factors such as unclear roles and responsibilities, lack of accountability, and low public participation are the main obstacles in achieving the goals of Good Local Governance.